Performance and digestibility of rabbits fed diets containing different levels of Prosopis laevigata pods - Mejia Haro, Ignacio; García Sánchez, Andrea Alejandra; Silos Espino, Héctor; Martínez Mireles, José Manuel; Arechiga Flores, Carlos Fernando; Silva Ramos, José Manuel (Acta Universitaria, 2023)
The objective of the study was to evaluate the effects on productive variables and in vivo digestibility of the inclusion of mesquite (Prosopis laevigata) pods in diets for growing rabbits. A production trial was carried out using thirty-six weaned-female rabbits in a completely randomized design assigned to one of three treatment diets containing different concentrations of ground mesquite pods (VMM): T1 (Diet without VMM), T2 (Diet 15% VMM), and T3 (Diet 30% VMM). Feed intake, weight gain, feed conversion, carcass yield, and in vivo digestibility of the diets were measured. Significant differences (p < 0.05) were found in daily weight gain, feed intake, carcass yield and dry matter digestibility between T1 and T3. Feed conversion ratio did not show significant differences among treatments (p < 0.05). Mesquite pods provide an adequate nutritional content to rabbit diets, and when used at 15%, they do not affect the productive variables and digestibility.